The deserving professional: job insecurity and gender inequality in the oil and gas industry*. (3rd April 2019) - Williams, Christine L.
ABSTRACT: Jobs have become increasingly insecure since the decline of the standard employment contract, a trend that is expected to continue in the future. Workers in all sectors of the economy, including scientists and engineers, face precarious working conditions today, as corporate downsizing and reorganisation result in routine layoffs. This paper investigates how job insecurity can contribute to gender inequality. Drawing on interviews with scientists and engineers conducted over a period of boom-and-bust at a multi-national oil company, I uncovered a discourse of 'the deserving professional.' This is a hegemonic discourse that identifies certain individuals—those who are under 50, native-born whites, and family breadwinners—as most deserving of keeping their jobs during periods of downsizing. I argue that the discourse of the deserving professional is used by workers to understand and in some cases justify what seem like arbitrary and biased decisions regarding layoffs. The discourse of the deserving professional also provides sociologists with insight into the future of white male domination of this industry.